1993
DOI: 10.1523/jneurosci.13-03-01258.1993
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of prohormone and proprotein convertases in the rat CNS: a comparative in situ hybridization analysis

Abstract: Posttranslational processing of proproteins and prohormones is an essential step in the formation of bioactive peptides, which is of particular importance in the nervous system. Following a long search for the enzymes responsible for protein precursor cleavage, a family of Kexin/subtilisin-like convertases known as PC1, PC2, and furin have recently been characterized in mammalian species. Their presence in endocrine and neuroendocrine tissues has been demonstrated. This study examines the mRNA distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
135
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(159 citation statements)
references
References 24 publications
23
135
1
Order By: Relevance
“…Seidah et al IFEBS Letters 379 (1996) study their possible coregulation [17]. For example, in the dentate gyrus of the hippocampus which expresses significant amounts of mRNAs coding for furin and PC1 [16] as well as PC7 [11] but not for PACE4 or PC5/6-B [28], the cognate processing enzymes may be reduced to the former two with the possible participation of PC1 in the processing of proBDNF (Fig. 4) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seidah et al IFEBS Letters 379 (1996) study their possible coregulation [17]. For example, in the dentate gyrus of the hippocampus which expresses significant amounts of mRNAs coding for furin and PC1 [16] as well as PC7 [11] but not for PACE4 or PC5/6-B [28], the cognate processing enzymes may be reduced to the former two with the possible participation of PC1 in the processing of proBDNF (Fig. 4) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Of the known convertases, only furin [10], PC5/6-B [12], a C-terminally extended isoform of PC5 [13] and possibly PC7 [11] contain a C-terminal transmembrane domain. Since all members of the convertase family can cleave precursors at the consensus type I cleavage site Arg-X-(Lys/Arg)-Argl [14], it became apparent that aside from cleavage specificity the cognate convertase(s) must also be correctly colocalized and possibly coregulated with their substrate within either the Trans Golgi Network (TGN) or in secretory granules [9,15,16]. Accordingly, studies on the colocalization of the neurotrophin mRNAs with those of the convertases and their coregulation revealed that more than one convertase can colocalize with the neurotrophins [17].…”
Section: Introductionmentioning
confidence: 99%
“…61,62 These enzymes are found in high concentrations in the pituitary gland and some brain regions. 63 Most of the endogenous peptides are secreted as inactive precursors and converted into an active form by PC1/3 and PC2. PC1/3 and PC2 response to opioid exposure appears to be biphasic.…”
Section: Opioid Effect On Camp-responsive Element-binding Proteinmentioning
confidence: 99%
“…Furin [244,245], PACE 4 [212] and PC6A [213] are expressed in most tissues and cells so far analysed (albeit at different levels from one cell type to the next). PC6B is expressed mainly in intestine [214], and expression of PCI and PC2 is restricted to endocrine and neuroendocrine tissues [205,207] including the brain [246][247][248].…”
Section: Tissue and Cellular Distribution Of The Convertasesmentioning
confidence: 99%
“…[205,209]. The mRNA distribution in the rat central nervous system has been studied very extensively by in situ hybridization [248]. PCI and PC2 were localized exclusively to neuronal cells, but PC2 was more widely expressed than PCI.…”
Section: Tissue and Cellular Distribution Of The Convertasesmentioning
confidence: 99%